Penerapan Tata Cara Pendaftaran Tanah di Indonesia Berdasarkan Peraturan Pemerintah No. 18 Tahun 2021 - Tirandika, Putu Reza Aditya; Resen, Made Gde Subha Karma (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 01 (2023), 2023)
The purpose of this study is to find and analyze the legal system governing land registration with respect to administrative power, land rights, housing units and land registration under Decree No. 18 of 2021 and to identify Decree No. 24 of 1997. to analyze. Identifying the legal impact of the administrative power, land rights, housing units and land registry on land registration by Decree No. 18 of 2021 and amendments to Decree No. 24 of 1997 after the enforcement of Decree No. 18 of 1997 and analysis effective 2021. This study is a normative legal study. The method used in this study is normative juridical with research specifications is descriptive analytical and data collection techniques using literature study with qualitative data analysis methods. To conclude, based on the findings of the investigation, that the Decree which is the legal basis for Decree No. 18 of 2021 on Land Rights, Housing and Management of Land Registry Units is still being implemented without government intervention. I can. Statutes that are canceled in advance. Decree No. 24 of 1997 on Land Registry. This differs in the notice period between the two decrees.